O plano estadual de educação do Estado do Maranhão: uma análise das interpretações sobre a gestão democrática em uma escola da rede pública - VERDE, Alexandre Viana (2022)
This research analyzes the translations made by a public school of the goal concerning the democratic management of the State Education Plan of the state of Maranhão. The concept of democratic management is discussed from the national historical and political processes and in the state of Maranhão, to contextualize where the goal concerning the democratic management of public education of the PEE (Law No. 10.099/2014) is translated and acted upon, thus enabling the identification of relations of articulations and/or disarticulations between the actual policy and the policy of use. The research is developed by the qualitative character, using the approach of the cycle and policy and the theory of performance, formulated by Stephen Ball and his collaborators (BOWE; BALL; GOLD, 1992; BALL, 1990; BALL, 1994; BALL; MAGUIRE; BRAUN, 2016) in the search for the affirmation of the policy developed in three arenas that distinguish and complement each other, based on the conception of the school as an institution with autonomy and the necessary capacity to translate and interpret the legal discourses. The bibliographical, documental and field research situates the object in space and time, also serving for the construction of relations between the theoretical and the empirical, accompanied by the application of questionnaires and semi-structured interviews with the members of the School Collegiate, enabling a variety of data from the most diverse segments that make up the school. The data collected were analyzed by the discourse theory formulated by Foucault (2012; 2014), whose premise states that discourses are historical and social constructions in constant transformation, formed by singularities and generalizations, which establish relationships with other discourses. The results of the research demonstrate the struggles of interests, contradictions and silencing in the policies that deal with the democratization of public education, making this educational principle a constant becoming. It is noteworthy that the context where the legal-normative discourse is translated and interpreted is singular, autonomous, and full of secondary adjustments. The de facto policy, translated and interpreted at school, presents articulations and disarticulations with the policy of use, demonstrating the school's ability to build its own discourses, distancing itself from the role it is given as an executor, the political actions in educational institutions are related to the discourses produced inside and outside the institutions. Thus, for the democratic management of public education to be ensured as a principle and practice, it becomes necessary to understand the school as a producer of politics, expanding its participation to the various contexts of educational policy so that the discourse between the actual policy and the policy of use becomes increasingly aligned.